The Role of Financial Management in Improving Business Sustainability - Ristanto (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
This study aims to analyze the role of financial management in improving business sustainability through a literature review approach of various relevant research results and scientific publications. The method used is a literature study by reviewing journal articles, books, and research reports that discuss financial management practices and their implications for business sustainability over the past ten years. The analysis process is carried out through identification, selection, and synthesis of research findings to obtain a comprehensive picture of financial management strategies that support business sustainability. The results of the study indicate that the implementation of effective financial management, including budget planning, cash flow management, cost control, financial risk management, and appropriate investment decision-making, plays a crucial role in maintaining operational stability and increasing business resilience to market dynamics. In addition, the use of digital financial technology contributes to the efficiency of financial management and expands access to business financing. The study findings also confirm that businesses that implement professional financial management practices tend to have better adaptability in the face of economic uncertainty. Therefore, strengthening financial management competency is a strategic factor in achieving business sustainability, especially for small and medium enterprises facing limited resources. This research is expected to serve as a conceptual reference for the development of management economics studies and provide recommendations for business actors in improving the quality of financial management for long-term business sustainability.